2010
DOI: 10.1002/asi.21429
|View full text |Cite
|
Sign up to set email alerts
|

Agency satisfaction with electronic record management systems: A large‐scale survey

Abstract: We investigated agency satisfaction with an electronic record management system (ERMS) that supports the electronic creation, archival, processing, transmittal, and sharing of records (documents) among autonomous government agencies. A factor model, explaining agency satisfaction with ERMS functionalities, offers hypotheses, which we tested empirically with a large-scale survey that involved more than 1,600 government agencies in Taiwan. The data showed a good fit to our model and supported all the hypotheses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…A fruitful future research direction will be to include BE and its determinants as predictors of these new dimensions of IT use. Furthermore, it will be important to study how IT use relates to performance at different levels of analysis, such as team performance (Fuller & Dennis, ), and contexts, such as e‐government (Venkatesh, Chan, & Thong, ), e‐commerce (Sia et al, ), health care (Hu, Hsu, Hu, & Chen, ; Venkatesh, Zhang, & Sykes, ), education (Booker et al, ), information science (Lee, Wei, & Hu, ), and consumer behavior (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A fruitful future research direction will be to include BE and its determinants as predictors of these new dimensions of IT use. Furthermore, it will be important to study how IT use relates to performance at different levels of analysis, such as team performance (Fuller & Dennis, ), and contexts, such as e‐government (Venkatesh, Chan, & Thong, ), e‐commerce (Sia et al, ), health care (Hu, Hsu, Hu, & Chen, ; Venkatesh, Zhang, & Sykes, ), education (Booker et al, ), information science (Lee, Wei, & Hu, ), and consumer behavior (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, service climate is recognized as predictor of interactional quality that may drive customer satisfaction and service performance (Chen, 2015). Research studies also validate the association between perceived service environment and satisfaction (Hu et al, 2010;Ryu, Lee, & Gon Kim, 2012). Chen et al (2015) and Wang (2009) found a significant impact of emotional regulation on interactional quality.…”
Section: Literature Reviewmentioning
confidence: 81%
“…These perceptions of role stressors may affect the quality of interaction interface with customer and can adversely influence the expected performance of employees. Role overload is acknowledged as one of the job stressors, where employees perceive high time pressure due to a number of responsibilities and commitments in their lives (Brown et al, 2005;Hu, Hsu, Hu, & Chen, 2010). Role overload is acknowledged as predictor of interactional quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, based on existing information sciences and mobile application research, we included items for two dependent variables, namely continued intention to use and brand loyalty. Intention in particular is a critical indicator of success of newly implemented information technologies and associated services (Hu et al, 2010(Hu et al, , 2005Hu et al, 2009). Prior research suggests aesthetic and colorful graphics positively influence consumers' continued intention to use and brand loyalty toward mobile applications (Scornavacca et al, 2006).…”
Section: Confirmatory Studymentioning
confidence: 99%